Innovation and experiential knowledge in firm exports : applying the initial U-Model - Geldres-Weiss, Valeska V.; Uribe-Bórquez, Claudina T.; Coudounaris, Dafnis T.; Monreal-Pérez, Joaquín (Elsevier, 2016)
Focusing on firm export activity as an important field within international business, this study corroborates the importance of experiential knowledge as the initial Uppsala model predicts. The model builds on the belief that experiential knowledge minimizes the risk and uncertainty of export operations. Additionally, the article examines a firm's capacity to widen this knowledge through its dynamic capacities, honing in on a firm's learning function. Thus, this article analyzes the role of innovation in exporting by investigating export product innovation and export market innovation, both strategic activities that allow experiential knowledge acquisition. The article uses a firm-level official dataset from a small developing country, Chile, examining data from 2006 to 2011. The results indicate, firstly, that experiential knowledge resulting from exporting to different and geographically distant markets increases the firm's export activity. Secondly, such export market innovation takes precedence over export product innovation.
Keywords: experiential knowledge; learning process; learning capacity; Chilean exporting firms; export operations; innovation; export; enterprises; export promotion; business; international corporations; internationalisation; international trade; small and medium-sized enterprises; experiential knowledge; international market; fi=Markkinointi|en=Marketing|